1992
DOI: 10.1084/jem.175.4.1147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GMP-140 (P-selectin) as a circulating plasma protein.

Abstract: GMP-140 is a 140-kD granule membrane protein, found in the alpha granules of platelets and the Weibel-Palade bodies of endothelial cells, that is surface expressed on cell activation and mediates neutrophil attachment. Cloning data for GMP-140 from an endothelial library predict a soluble form of the protein, the transcription message for which is also found in platelets. In this study, we report the detection by enzyme-linked immunosorbent assay of soluble GMP-140 in plasma centrifuged for 3 h at 100,000 g (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
0
6

Year Published

1995
1995
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(139 citation statements)
references
References 15 publications
(35 reference statements)
3
130
0
6
Order By: Relevance
“…Measuring soluble P-selectin, which originates from both platelets and endothelial cells, is proposed as a marker of increased membrane-bound P-selectin expression, attributable to vascular dysfunction and/or platelet activation, and may provide information on in vivo interactions among vascular and circulating cells. 6,7,10 In vitro experiments revealed that P-selectin induced tissue factor expression in human circulating monocytes and suggest that an increase in plasma P-selectin may have as a consequence the induction of a hypercoagulable state. 19 Plasma TM level appears to be initially increased with acute vascular injury, perhaps through cleavage from the cell surface, and is then decreased with subsequent downregulation of production after chronic vessel injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring soluble P-selectin, which originates from both platelets and endothelial cells, is proposed as a marker of increased membrane-bound P-selectin expression, attributable to vascular dysfunction and/or platelet activation, and may provide information on in vivo interactions among vascular and circulating cells. 6,7,10 In vitro experiments revealed that P-selectin induced tissue factor expression in human circulating monocytes and suggest that an increase in plasma P-selectin may have as a consequence the induction of a hypercoagulable state. 19 Plasma TM level appears to be initially increased with acute vascular injury, perhaps through cleavage from the cell surface, and is then decreased with subsequent downregulation of production after chronic vessel injury.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several reports have demonstrated that a soluble form of P-selectin is present in the normal circulation. 7 Previous investigations related to thrombotic, inflammatory, and atherosclerotic disorders have suggested that plasma P-selectin may reflect endothelial cell injury and platelet activation. 8 -10 There is, however, no report concerning the relationship between PH and P-selectin.…”
mentioning
confidence: 99%
“…27 Sections were deparaffinized, rinsed in xylene, and rehydrated. They were blocked with 3% H 2 O 2 , washed in water, treated with 2% ovalbumin in PBS, washed in PBS, and incubated with the primary antibodies at 37°C for 2 hours.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Upon activation of platelets or endothelial cells, P-selectin is quickly expressed on the surface membrane, where it mediates both the interaction of activated platelets with leucocytes, and leucocyte rolling on the activated endothelium 10 . Circulating degranulated platelets rapidly shed surface P-selectin 11 , producing the circulating plasma protein soluble P-selectin (sP-selectin) 12 . Although P-selectin is present in both platelets and endothelial cells, several authors have concluded that platelets are the major source of sP-selectin in plasma 13 -15 .…”
Section: Introductionmentioning
confidence: 99%